2004
DOI: 10.1111/j.1440-1754.2004.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a nutrition audit in a tertiary paediatric hospital: Implications for service improvement

Abstract: Barriers to nutritional assessment can lead to failure to diagnose and treat both over- and under-nutrition, thereby affecting quality of patient care, and may have financial implications for hospitals. Suggestions for service improvement include provision of accurate equipment, adequate training of staff undertaking nutritional assessments and clear definitions of staff responsibilities in all aspects of the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 11 publications
2
33
2
Order By: Relevance
“…Frequency of addressing overweight/obesity during the hospitalization (4%) and specifically percentage of patients for whom a nutrition consult was performed (2.7%) were lower in our study compared with rates reported by both O’Connor (4.8%) 10 and Sleeper (24%). 11 This is likely, at least in part, a reflection of hospital protocol.…”
Section: Discussioncontrasting
confidence: 82%
“…Frequency of addressing overweight/obesity during the hospitalization (4%) and specifically percentage of patients for whom a nutrition consult was performed (2.7%) were lower in our study compared with rates reported by both O’Connor (4.8%) 10 and Sleeper (24%). 11 This is likely, at least in part, a reflection of hospital protocol.…”
Section: Discussioncontrasting
confidence: 82%
“…This finding is not new: the nutrition audit by Hartman [22] in Israel showed that 24% of the children had no weight recorded during hospitalization and the Australian report of O'Connor et al [23] described that only 27% of the patients had both their weight and height recorded. Interestingly, we were surprised to find data on weight and/or height in only 54% of the transferred children, although this figure is still higher than the 8% found in a Dutch study on communication between general practitioners and specialists concerning adults with head and neck cancer [24].…”
Section: Discussionmentioning
confidence: 99%
“…From a study in which GPs and paediatricians attempted to identify child weight status from visual images alone, we know that clinical impression results in under‐recognition of overweight and obesity 11 . A recent audit in an Australian tertiary paediatric hospital found that only 27% of patients had both height/length and weight recorded on their bed chart, and seven out of 12 wards had inaccurate stadiometers 12 . While similar information is not available for GPs, it seems unlikely that they would do systematically better in these areas.…”
Section: Australian Guidelines For Detecting Childhood Overweight Anmentioning
confidence: 99%